Do the Interactions between Glucocorticoids and Sex Hormones Regulate the Development of the Metabolic Syndrome? - Alemany, Marià (Frontiers in Endocrinology, 2012)
The metabolic syndrome is basically a maturity-onset disease. Typically, its manifestations begin to flourish years after the initial dietary or environmental aggression began. Since most hormonal, metabolic or defense responses are practically immediate, the procrastinated response don't seem justified. Only in childhood, the damages of the metabolic syndrome appear with minimal delay. Sex affects the incidence of the metabolic syndrome, but this is more an effect of timing than absolute gender differences, females holding better than males up to menopause, when the differences between sexes tend to disappear. The metabolic syndrome is related to an immune response, countered by a permanent increase in glucocorticoids, which keep the immune system at bay but also induce insulin resistance, alter the lipid metabolism, favor fat deposition, mobilize protein and decrease androgen synthesis. Androgens limit the operation of glucocorticoids, which is also partly blocked by estrogens, since they decrease inflammation (which enhances glucocorticoid release). These facts suggest that the appearance of the metabolic syndrome symptoms depends on the strength (i.e. levels) of androgens and estrogens. The predominance of glucocorticoids and the full manifestation of the syndrome in men are favored by decreased androgen activity. Low androgens can be found in infancy, maturity, advanced age, or because of their inhibition by glucocorticoids (inflammation, stress, medical treatment). Estrogens decrease inflammation and reduce the glucocorticoid response. Low estrogen (infancy, menopause) again allow the predominance of glucocorticoids and the manifestation of the metabolic syndrome. It is postulated that the equilibrium between sex hormones and glucocorticoids may be a critical element in the timing of the manifestation of metabolic syndrome-related pathologies.